Development of new β Ti-10-Mo-Mn alloys for biomedical applications - Lourenço, Mariana Luna [UNESP]; Correa, Mariana Rocha [UNESP]; de Almeida, Gerson Santos [UNESP]; Kuroda, Pedro Akira Bazaglia [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Grandini, Carlos Roberto [UNESP] (Elsevier, 2024)
Metallic biomaterials play a crucial role in various biomedical applications, particularly in developing implants and prostheses. Hence, this study aimed to produce and analyze the structure, microstructure, hardness, and preliminary cytotoxicity of Ti-10Mo-xMn system alloys (with x ranging from 0 to 8 wt%) intended for biomedical applications as biomaterials. The alloys underwent thorough characterization, including chemical composition analysis through EDS measurements, mapping, and density assessments. Structural and microstructural analyses were conducted using x-ray diffraction (XRD), Rietveld refinement, optical (OM), and scanning electron microscopy (SEM), while Vickers microhardness testing provided insights into mechanical properties. Rapid cytotoxicity tests via MTT were also performed to assess biocompatibility. Results indicated that the produced alloys exhibited good quality and homogeneity regarding chemical composition. Adding Mn to the Ti-10Mo alloy facilitated the formation of the β phase, transforming it from a biphasic (α + β) to a single-phase alloy. Moreover, Mn-induced reductions in lattice parameters and average crystallite size of the β phase were observed due to the smaller atomic radius of substituting Mn than Ti. Despite a decrease in hardness attributed to β phase formation, all alloys demonstrated non-cytotoxic behavior in cell adhesion and viability assays, with values exceeding 70 %. Overall, these findings highlight the potential of Ti-10Mo-xMn alloys as viable biomaterials, warranting further exploration and development in biomedical engineering.
Keywords: Biomaterials; Materials characterization; Ti alloy